Neuroblastoma RAS viral oncogene homolog mRNA is differentially spliced to give five distinct isoforms: implications for melanoma therapy. Issue 5 (October 2019) - Duggan, Megan C.; Regan-Fendt, Kelly; Olaverria Salavaggione, Gonzalo N.; Howard, John Harrison; Stiff, Andrew R.; Sabella, Julia; Latchana, Nicholas; Markowitz, Joseph; Gru, Alejandro; Tridandapani, Susheela; Eisfeld, Ann-Kathrin; de la Chapelle, Albert; et al.
Abstract : Neuroblastoma RAS viral oncogene homolog is a commonly mutated oncogene in melanoma, and therapeutic targeting of neuroblastoma RAS viral oncogene homolog has proven difficult. We characterized the expression and phenotypic functions of five recently discovered splice isoforms of neuroblastoma RAS viral oncogene homolog in melanoma. Canonical neuroblastoma RAS viral oncogene homolog (isoform-1) was expressed to the highest degree and its expression was significantly increased in melanoma metastases compared to primary lesions. Isoform-5 expression in metastases showed a significant, positive correlation with survival and tumours over-expressing isoform-5 had significantly decreased growth in a xenograft model. In contrast, over-expression of any isoform resulted in enhanced proliferation, and invasiveness was increased with over-expression of isoform-1 or isoform-2. Downstream signalling analysis indicated that the isoforms signalled differentially through the mitogen-activated protein kinase and PI3K pathways and A375 cells over-expressing isoform-2 or isoform-5 showed resistance to vemurafenib treatment in vitro . The neuroblastoma RAS viral oncogene homolog isoforms appear to play varying roles in melanoma phenotype and could potentially serve as biomarkers for therapeutic response and disease prognosis. Abstract : Supplemental Digital Content is available in the text.